Development of Student Civic Competence Through Scouting Courses as Strengthening the Young Generation Character - Wachid Pratomo; Dwi Wijayanti (JED (Jurnal Etika Demokrasi), 2020)
The purpose of this study Is to determine the pattern of civic competence coaching for students through Scouting Education as a reinforcement of young characters in the USSD FKIP PGIP Study Program. This study used qualitative research with a case study method. This study consists of the formulation of the problems namely: civic competence in the context of Scouting Education, Scouting learning process in fostering student civic competence, obstacles and solutions in fostering civic competence through Scouting Education, the role of Scouting Education in fostering student civic competence. In collecting data researchers used three techniques namely observation, interviews, and documentation. Data analysis uses an interactive model. This research produces several findings, namely: (1) Civic competence in the context of Scouting Education: Citizenship knowledge includes understanding democracy, understanding defending the country, understanding obligations and rights. Citizenship skills include three skills namely managerial, organizational, and scout skills. Citizenship character is in the form of character contained in the tri satya and dasa dharma. (2) Knowledge is fostered by providing the task of finding information related to Scouting to be understood and poured back on the exam, skills are fostered by learning by doing with the team system, and character is fostered by instilling the values of tri satya characters and dasa dharma with habituation and the system among. (3) Obstacles in the development of civic competence that is students still feel shy, less responsible, arriving late. The solution is to be assertive and apply reward and punishment in learning process.Keywords: Development of Civic Competence, Scouting Education, Strengthening Character of Young GenerationTujuan penelitian ini adalah untuk mengetahui pola pembinaan civic competence mahasiswa melalui Pendidikan Kepramukaan sebagai penguatan karakter muda di Prodi PGSD FKIP UST. Penelitian ini menggunakan penelitian kualitatif dengan metode studi kasus. Penelitian ini terdiri dari rumusan masalah yaitu: civic competence dalam konteks Pendidikan Kepramukaan, proses pembelajaran Pendidikan Kepramukaan dalam membina civic competence mahasiswa, kendala dan solusi dalam pembinaan civic competence melalui Pendidikan Kepramukaan, peran Pendidikan Kepramukaan dalam membina civic competence mahasiswa. Dalam pengumpulan data peneliti menggunakan tiga teknik yaitu observasi, wawancara, dan dokumentasi. Analisis data menggunakan model interaktif. Penelitian ini menghasilkan beberapa temuan, yaitu: (1) Civic competence dalam konteks Pendidikan Kepramukaan: pengetahuan kewarganegaraan mencakup pemahaman demokrasi, pemahaman bela negara, pemahaman kewajiban dan hak. Keterampilan kewarganegaraan mencakup tiga keterampilan yaitu keterampilan manajerial, organisatorik, dan keterampilan pramuka. Karakter kewarganegaraan berwujud karakter yang terdapat dalam tri satya dan dasa dharma. (2) Pengetahuan dibina dengan memberikan tugas untuk mencari informasi terkait Kepramukaan untuk dipahami dan dituangkan kembali pada ujian, keterampilan dibina dengan learning by doing dengan sistem beregu, dan karakter dibina dengan menanamkan nilai-nilai karakter tri satya dan dasa dharma dengan pembiasaan dan sistem among. (3) Kendala dalam pembinaan civic competence yaitu mahasiswa masih merasa malu, kurang bertanggung jawab, datang terlambat. Solusi berupa bersikap tegas dan menerapkan reward and punishment dalam proses pembelajaranKata Kunci: Pembinaan Civic Competence, Pendidikan Kepramukaan, Penguatan Karakter Generasi Muda